2016
DOI: 10.1111/cdev.12692
|View full text |Cite
|
Sign up to set email alerts
|

Infant Attachment and Maternal Sensitivity in the Arab Minority in Israel

Abstract: This study is the first to examine infant-mother attachment in the Arab culture. Eighty-five Arab 1-year-old infants from Israel were observed in the strange situation, and maternal sensitivity was assessed from home observations. Supporting attachment theory's normativity hypothesis, no differences were found between the Arab-Israeli attachment distribution and Jewish-Israeli, Western, and non-Western distributions when examined at the two-way secure versus insecure level, although a few differences emerged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…agree with Keller and others that warmth and sensitive responsiveness are separate constructs (Keller, Lohaus, Völker, Elben, & Ball, ), warmth is still considered an important aspect of this type of care. Warmth is included in the definition of sensitive responsiveness in seven of the eight most used observational instruments of parental sensitivity (Mesman & Emmen, ), and affection is a prominent dimension of maternal sensitivity in the Maternal Behavior Q‐sort (Pederson & Moran, ), which is still being used (e.g., Zreik, Oppenheim, & Sagi‐Schwartz, ).…”
Section: Warmth As An Essential Component Of Sensitive Responsivenessmentioning
confidence: 99%
“…agree with Keller and others that warmth and sensitive responsiveness are separate constructs (Keller, Lohaus, Völker, Elben, & Ball, ), warmth is still considered an important aspect of this type of care. Warmth is included in the definition of sensitive responsiveness in seven of the eight most used observational instruments of parental sensitivity (Mesman & Emmen, ), and affection is a prominent dimension of maternal sensitivity in the Maternal Behavior Q‐sort (Pederson & Moran, ), which is still being used (e.g., Zreik, Oppenheim, & Sagi‐Schwartz, ).…”
Section: Warmth As An Essential Component Of Sensitive Responsivenessmentioning
confidence: 99%
“…For example, SSP studies in Israel have consistently shown more children in the C than in the A category (e.g., Koren-Karie, Oppenheim, Dolev, Sher, & Etzion-Carasso, 2002;Sagi, Koren-Karie, Gini, Ziv, & Joels, 2002). A recent study that reported Arab-Israeli SSP distribution also found more children in the C category than in the A category (Zreik, Oppenheim, & Sagi-Schwartz, 2017). Thus, diverse cultural norms may partly explain why C infants dominate the insecure category for a Japanese sample and some others, but this does not negate the applicability of the measure as a whole.…”
Section: Historical Controversy: Japanese Strange Situation Studiesmentioning
confidence: 99%
“…Next, to assess the attunement of mother-infant interactions, mothers were invited to join their infants on the mattress and play with them for 10 minutes as they usually did, but without any toys or a pacifier. This type of unstructured "social play" is common in research of mother-infant and mother-child interactions (e.g., Miller & Harwood, 2002;Zreik et al, 2017). As we were interested in examining maternal sensitivity in the modality of touch and holding, we asked the mothers to pick up the infant from the mattress and put the infant down at least once during the interaction.…”
Section: Methodsmentioning
confidence: 99%